Grass and Legume Hays for Sheep: Intake, in vivo Digestibility, and in situ Degradability - Otoni, Iana Mara Medeiros; Silva, Janaina Lima da; Ribeiro, Karina Guimaraes; Pereira, Odilon Gomes; Silva, Thiago Carvalho da; Siva, Luiz Fernando Costa e; Filho, Sebastiao de Campos Valadares (Journal of Agricultural Studies, 2021)
The objective of this study was to evaluate nutrient intake, in vivo digestibility, and in situ degradability of different cultivars of hay (i.e., [Jiggs] and [Tifton-85] bermuda grass (Cynodon spp.) and [alfalfa] (Medicago sativa) and [stylo] Campo Grande (Stylosanthes sp.)) and nitrogen balance in sheep. We used eight rumen-cannulated F1 Santa Ines × Dorper castrated male sheep with body weights of 35.0 kg in a double 4 × 4 Latin Square experimental design. The intake and total apparent digestibility of nutrients were higher (P<0.05) for alfalfa than for stylo hay. The in vivo dry matter (DM) digestibility of Jiggs (47.6%), Tifton-85 (53.4%), stylo (29.3%), and alfalfa (53.2%) hays and in situ DM degradability were equivalent in the range of 7.6 to 63.2 h of degradation. The in vivo neutral detergent fiber (NDFap) digestibility of Jiggs (53.7%), Tifton-85 (64.4%), stylo (42.2%), alfalfa (56.2%), and in situ NDFap degradability were equivalent from 37.3 h. Nitrogen balance was negative only in animals fed stylo hay. Alfalfa hay provides a higher nutrient intake than other hays. The alfalfa and bermuda grass hays used in sheep diets presented better digestibility than stylo hay. The results are suitable to predict in vivo digestibility from in situ degradability parameters.